Theoretical and experimental study of agricultural spraying using CFD - Freitas Fogal, Marcelo Luiz [UNESP]; Padilha, Alcides [UNESP]; Scalon, Vicente Luiz [UNESP] (Abcm Brazilian Soc Mechanical Sciences & Engineering, 2014)
This paper presents a computational fluid dynamics (CFD) application about the axial fan design used in an agricultural spraying system with a theoretical and experimental analysis of comparative results between the characteristic curves of a fan for several rotations and numerical results for the influence of blade attack angle variation and optimization of the spraying system, both for a same rotation. Flow was considered three-dimensional, turbulent, isothermal, viscous and non-compressible in a steady state, disregarding any influence of the gravity field. The average turbulent field was obtained from the application of time average where the turbulence model required for closing the set of equations was the k-E model. Resolution of all connected phenomena was achieved with the help of a fluid dynamics computer, CFX, which uses the finite volumes technique as a numerical method. In order to validate the theoretical analysis, an experiment was conducted in a circular section of a horizontal wind tunnel, using a Pitot tube for pressure readings. The main results demonstrate that the methodology used, based on CFD techniques, is able to reproduce the phenomenological behavior of an axial fan in a spraying system because results were very reliable and similar to experimentally measured ones.
Keywords: Axial fan; Characteristic curves; Computational fluid dynamics; Turbulence model; Wind tunnel